Learning Number Patterns through Batik and Webbing Motifs: An Ethnomathematics Study in Kudus - Lestari, Mulyaningrum; Malasari, Putri Nur (Universitas Islam Negeri Sunan Kudus, 2024)
Number pattern learning lacks a link to everyday life. This research aims to find the concept of number patterns in batik and weaving motifs in the Japanese village of Kudus Regency. Qualitative approach with ethnographic model was used in this research. The subjects of this research were woven craftsmen in Japanese village, batik craftsmen in Alfa Shoofa Batik Kudus and Muria Batik Kudus. Data collection techniques used interviews, observation, and documentation with research instruments in the form of interview guidelines, documentation, and field notes. The results of the research found the concept of arithmetic sequence in Kudus batik motifs. Kudus batik motifs form an arithmetic sequence with a difference of 6 and a difference of 3. In addition, odd and even number sequence patterns were found. Meanwhile, in the weaving of the Japanese village community, an arithmetic sequence with the formula Un = 2n -1 (odd number pattern) and Un = 2n (even number pattern) was found. The research findings can be developed as a learning resource for number patterns in mathematics learning. Pembelajaran pola bilangan kurang mengaitkan dengan kehidupan sehari-hari. Penelitian ini bertujuan untuk menemukan konsep pola bilangan pada motif batik dan anyaman di desa Jepang Kabupaten Kudus. Pendekatan kualitatif dengan model etnografi digunakan dalam penelitian ini. Subjek penelitian ini adalah pengrajin anyaman di desa jepang, pengrajin batik di Alfa Shoofa Batik Kudus dan Muria Batik Kudus. Teknik pengumpulan data menggunakan teknik wawancara, observasi, dan dokumentasi dengan instrumen penelitian berupa pedoman wawancara, dokumentasi, dan catatan lapangan. Hasil penelitian ditemukan konsep barisan aritmatika pada motif batik Kudus. Motif batik Kudus membentuk barisan aritmatika dengan beda 6 dan beda 3. Selain itu, ditemukan pola barisan bilangan ganjil, dan genap. Sementara pada anyaman masyarakat Desa Jepang ditemukan barisan aritmatika dengan rumus Un = 2n -1 (pola bilangan ganjil) dan Un = 2n (pola bilangan genap). Temuan penelitian dapat dikembangkan sebagai sumber belajar pola bilangan pada pembelajaran matematika.